Types of Assessments Based on Bloom’s Taxonomy in the Merdeka Curriculum Book English for Change for Phase F of XI Class - Nurmawati, Nurmawati; Budi Santosa, Rochmat (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
This study investigates the types of assessments presented in the Merdeka Curriculum English textbook English for Change for Phase F (Grade XI), using Bloom’s Taxonomy as the analytical framework. As textbooks play a central role in translating curriculum goals into classroom practice, it is critical to examine whether their assessments promote a balanced range of cognitive skills. A qualitative content analysis was conducted to identify and categorize 74 assessment tasks according to the six levels of Bloom’s revised taxonomy: Remembering, Understanding, Applying, Analyzing, Evaluating, and Creating. The findings show that while the textbook incorporates both lower-order and higher-order thinking skills, a greater emphasis is placed on the former—particularly Understanding and Applying. Tasks requiring critical thinking and creativity (Evaluating and Creating) are included but appear less frequently. These results suggest that while the textbook aligns broadly with the Merdeka Curriculum’s competency-based philosophy, enhancements could be made to deepen cognitive engagement. Implications are discussed for teachers, curriculum developers, and researchers seeking to improve the design and implementation of assessments in EFL contexts.